ANALISIS PERENCANAAN SUMBER DAYA MANUSIA YANG EFEKTIF - H. Abdul Rasul (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2017)
Planning HRD represents former activity from all existing activity in course of HRDM. Planning in management play a part and the function which of vital importance to determine organizational direction. Organizational efficacy determined by effective planning HRD. There are various factor influencing effectivity of planning HRD, what very sliver its bearing with strategy organ izational. Correlate planning HRD into formulation step in strategy implementation, organization earn to improve opportunity own the right people at the right place and time. Result from this integration in substansial own important meaning from organizational importance.